Amadeus [videorecording (DVD)] - Forman, Miloš; Zaentz, Saul; Abraham, F. Murray; Hulce, Tom, 1953-; Berridge, Elizabeth, 1962-; Callow, Simon, 1949-; Dotrice, Roy, 1923-2017; Ebersole, Christine; Jones, Jeffrey, 1947-; Kay, Charles, 1930-2025; Ondříček, Miroslav, 1934-2015; Von Brandenstein, Patrizia; et al. (Distributed by Warner Home Video, 2009)
When Mozart arrives at the court of Emperor Joseph II, court composer Antonio Salieri is horrified to discover that the godlike musical gifts he desires himself have been bestowed on a bawdy joker. Mad with envy, he plots to destroy Mozart by any means.